THE WAR DEPARTMENT CLASSIFICATION OF ACCOUNTS. - Read, W. H. (The Accounting Review, 1947)
Abstract The purpose of this article is to describe the U.S. War Department account classification and to show the use made of each element of the code, as of July 1947. It must be remembered that the War Department comprises only one component of the U.S. government and, consequently, must necessarily follow accounting procedures prescribed by the U.S. Bureau of the Budget and the U.S. Treasury Department. At the same time it must prepare its accounts to suit the eagle eye of the U.S. General Accounting Office which is to audit the accounts of the approximately twelve hundred army disbursing officers. Consequently, War Department account classification is a result of normal federal procedure plus additions required by operating conditions within the department. The complete classification explained in this article is designed to provide a basis for budgeting, accounting and reporting, designating accountability and responsibility, and exercising managerial control over finances. Each transaction of the U.S. government is related to some one fund of which there are three major categories, namely, the general fund, special funds and trust funds.